Integrating DevSecOps into Information Security for Software Development: A Systematic Review - Monzon Llanos, Jhonatan Efrain (2026)
The increase in cyber threats and the need to integrate security into the software lifecycle have driven the adoption of DevSecOps as an evolution of DevOps. This study aimed to analyze the benefits, challenges, and trends of integrating DevSecOps tools into information security applied to software development. For this purpose, the PRISMA methodology was used and searches were carried out in academic databases such as arXiv, Google Scholar, SCOPUS, and IEEE Xplore. This enabled the selection and analysis of 18 significant articles published between 2020 and 2025. The findings show that implementing DevSecOps allows for the early identification of vulnerabilities, improves the resilience of systems, and fosters a shared security culture among development groups. However, challenges related to tool compatibility, organizational development, and the need for integrative frameworks persist. Thus, DevSecOps is emerging as a key approach to optimizing software continuity and reliability. However, its long-term sustainability depends on future research investigating predictive models, evaluation metrics, and the use of technologies such as artificial intelligence and advanced automation.